DETERMINASI JOB CRAFTING, INNOVATIVE WORK BEHAVIOR, DAN EFIKASI DIRI TERHADAP KINERJA PEGAWAI APARATUR SIPIL NEGARA - Deni Tri Mulyono; Susanti Dwi Ilhami (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This research is motivated by the importance of improving the performance of State Civil Apparatus (ASN) through managing individual factors relevant to work dynamics. The purpose of this research is to analyze the influence of job crafting, innovative work behavior, and self-efficacy on the performance of ASN employees in the Regional Apparatus Organization (OPD) of Rembang District, Rembang Regency. The research method uses a descriptive quantitative approach with data collection techniques through questionnaires. The research sample consisted of 54 respondents determined by the total sampling method. Data analysis was carried out using Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software version 4.1.1.2. The analysis stages include evaluation of the outer model, inner model, and model fit test. The results show that the three independent variables have a positive and significant effect on employee performance. Job crafting is proven to increase employee work effectiveness, innovative work behavior contributes to creating innovative work solutions, while self-efficacy strengthens employee confidence in completing tasks. In conclusion, job crafting, innovative work behavior, and self-efficacy are important factors that can improve the performance of ASN employees in Rembang District, Rembang Regency. These findings offer practical implications for human resource management within local governments to foster an adaptive, innovative, and performance-oriented work culture